Increased urinary nitrite, a marker of nitric oxide, in active inflammatory bowel disease. Issue 2 (2001) - Goggins, Michael G.; Shah, Syed A.; Goh, Jason; Cherukuri, Anil; Weir, Donal G.; Kelleher, Dermot; Mahmud, Nasir
Abstract : Background : Nitric oxide (NO) production is increased in inflammatory bowel disease (IBD), and measurement of NO metabolites may be useful for monitoring disease activity. Aims and objectives : To characterise urinary nitrite levels, a stable metabolite of NO, in IBD and to evaluate its potential as a marker of disease activity. Methods : Twelve-hour urinary nitrites were measured by the microplate assay method in 46 patients with IBD (active; n = 32). Urinary samples from 16 healthy individuals served as controls. Results : Increased levels of urinary nitrites were found in patients with active IBD compared with those with inactive IBD. Twenty-eight out of 32 patients (87.5%) with active IBD had detectable levels of nitrite in their urine as compared with 2/14 (14.3%) patients with inactive IBD. None of the 16 healthy controls had detectable urinary nitrite. Twelve-hour urinary nitrite in active compared with inactive IBD: 5 Ī 0.7 versus 0.1 Ī 0.04 μ mol( P < 0.05 ) . There was good correlation between urinary nitrite and some markers of disease activity in IBD such as C-reactive protein and microalbuminuria but not with erythrocyte sedimentation rate. Conclusions : Increased levels of nitrite were detected in urine of patients with active IBD, consistent with increased NO synthesis. This simple assay may be exploited as a potential marker of disease activity in IBD.